(untitled) (American Journal of Management, 2023)
A study published in 2022 identified the top 10 Countries with the best healthcare as (1) Denmark, (2) Switzerland, (3) Australia, (4) France, (5) Singapore, (6) The United Kingdom, (7) Germany, (8) Canada, (9) Austria, and (10) Japan. The United States spends more money per capita on healthcare than any other country. Still, the United States healthcare did not make the top twenty. Another study published in 2021 ranked the US last in access to healthcare, equity, and outcomes among the 11 high income countries, despite spending a far greater share of its GDP on healthcare (Luhby, 2021). The World Health Organization’s ranking of the world’s health systems put France at #1and the United States at #37 (World Health Organization, 2019). This paper examines a broad IT related healthcare literature and seven key IT tools and technologies that should be integrated into a comprehensive U.S. healthcare system. Properly integrating these IT tools and technologies should narrow the gap and improve the five critical success factors: Quality, Access, Efficiency, Equity, and Healthy lives.